Ethics of Communication on Social Media in The Perspective of The Interpretation of Ibn Kathir - Haerudin Haerudin; Iyad Suryadi; Helmawati Helmawati (Universitas Darussalam Gontor, 2025)
The phenomenon of using social media has become common in many circles, therefore, it is required to be smart and wise in using it, in Islam the ethics of communication must be in accordance with the sharia, namely emphasizing the Islamic elements and also with language that shows Islam and Islamic communication. This research is a type of qualitative descriptive research using library research. The data collection technique is by docmentation and observation. Meanwhile, the data analysis is by data reduction, data presentation and conclusion drawn. The results of the study show that communication ethics in social media according to the perspective of Tafsir Ibn Katsir emphasizes relevant Qur'anic principles. In Tafsir Ibn Kathir provides a strong foundation through the interpretation of verses of the Qur'an related to speech, behavior, and social interaction, including the first, in Surah An nisaa verse 5 which emphasizes the importance of speaking with good words to improve morals, the second, Al Ahzab verse 70 about emphasizing demanding good words, honesty, politeness, and responsibility in expressing opinions and respecting the existence of others in the digital space, third, Al-Hujurat verses 11–12, which emphasizes the prohibition of blasphemy, gossip, and prejudice that must be maintained for a Muslim.